2021
DOI: 10.1080/14397595.2021.1879429
|View full text |Cite
|
Sign up to set email alerts
|

Good response to methotrexate is associated with a decrease in the gene expression of ABCG2, a drug transporter, in patients with rheumatoid arthritis

Abstract: Background Methotrexate (MTX) is an anchor drug in the treatment of rheumatoid arthritis (RA). We previously performed a cross-sectional, observational study and reported an association between the gene expression level of the drug transporter ABCG2/BCRP (breast cancer resistance protein) and RA disease control in patients receiving MTX.Methods We designed a prospective study in two medical centers in Japan to con rm the association of ABCG2 gene expression level with the clinical response to MTX in MTX-naive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They are essential for developing the immune system and regulation ( 96 ). In addition, miRNAs have high tissue specificity and are expressed differentially in various tissues ( 97 ). An analysis of circulatory miRNAs comprising 50 RA patients showed that miR-126-3p, miR-221-3p, let-7d-5p, miR-431-3p, miR-24-3p, and miR-130a-3p were significantly elevated in the serum of RA patients and “at-risk individuals,” as well as miR-130a-3p combined with the remaining five to yield a higher AUC.…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…They are essential for developing the immune system and regulation ( 96 ). In addition, miRNAs have high tissue specificity and are expressed differentially in various tissues ( 97 ). An analysis of circulatory miRNAs comprising 50 RA patients showed that miR-126-3p, miR-221-3p, let-7d-5p, miR-431-3p, miR-24-3p, and miR-130a-3p were significantly elevated in the serum of RA patients and “at-risk individuals,” as well as miR-130a-3p combined with the remaining five to yield a higher AUC.…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…BCRP transported both methotrexate and polyglutamylated methotrexate and participated in methotrexate resistance ( 44 ). Good response to methotrexate was associated with a decrease in expression of BCRP in RA patients ( 45 ), while the association of BCRP polymorphisms with the effectiveness of methotrexate was not observed ( 46 ), suggesting that BCRP expression was not genetically determined, but might be associated with environmental factors ( 45 ). BCRP inhibition could be a strategy for overcoming nonresponse to methotrexate.…”
Section: Csdmardsmentioning
confidence: 99%
“…While SLC19A1 and SLC46A1 are facilitating cellular entry, there are members of the ATP-binding cassette transporter family, namely ABCB1 , 15 ABCC2 and ABCG2 , that are assumed to limit methotrexate bioavailability by active efflux of the molecule. 16 MTX response depends on the expression of ABCG2 (breast cancer resistance protein, BCRP) 17 and it has been shown that genetic variants influenced MTX plasma levels in pediatric patients. 18 Moreover, ABCG2 was associated with MTX discontinuation in a clinical PGx model.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on C3435T polymorphism had diverging results. The 3435C allele was associated with increased toxicity, 17 while the 3435T allele has been associated with high disease activity and increased ADRs, 20 non-response, 21 and with a low disease activity score 22 and PharmGKB 44 cites that carriers of the 3435T allele might have an increased risk of toxicity. With these inconclusive findings reported in the literature, it is difficult to decide on the impact the variants in ABCB1 would have on MTX transport, thereby making a predictive decision impossible.…”
Section: Introductionmentioning
confidence: 99%